Quantitative and Qualitative Analysis of Palatal Rugae Patterns in Bhopal Division: A Retrospective Cross-Sectional Study - Narendra Patel; Rishi Thukral; Heeralal Chokotiya; Ruchi Gulati; Dharika Patel; Satendra Singh Dhakad (Journal of Pharmacy and Bioallied Sciences)
Objective: The goal of this investigation is to assess the palatal rugae patterns in male and female participants from the Bhopal Division population. Material and Methods: A randomly selected cohort of 104 individuals, consisting of 47 males and 57 females, was included in the study. Both metric and non-metric characteristics of the palatal rugae were documented and analyzed using two-sample t-tests and chi-square tests, with a significance threshold set at 5%. Results: No significant difference was observed in the total number of rugae between genders. However, the mean number of primary rugae was significantly higher in males (P = 0.038). In contrast, females exhibited a higher mean number of vertical (P < 0.001) and fragmentary rugae (P = 0.004), with these differences achieving statistical significance. Conclusion: The rugae pattern demonstrates potential as a gender-differentiating characteristic, serving as a supplementary method to traditional techniques such as cranial anthropometry and dental analysis.